Code Switching and Viewers’ Attitude Toward Interviews with President Susilo Bambang Yudhoyono (Sby) (An Analysis of Interview Transcript from Www.Presidenri.Go.Id) - Ricky Nurhaki (Universitas Pendidikan Indonesia (UPI), 2013)
This study explores some important issues, namely the occurrences of code switching types, function, and the language attitudes of English and Indonesian students department toward the use of code switch in the interview with President Susilo Bambang Yudhoyono (SBY). The data were collected through distributing questionnaires to respondents of the English students (15 persons) and the Indonesian students (15 persons) of UPI and compiling the documents of interview transcripts taken from www.presidenri.go.id. Some theories were used to analyse the data, namely Poplack (1980) was used to identify types of code switching, Koziol (2000) was applied to investigate functions of Code Switching, while Lambert (1967) was implemented to find out the attitude of the viewers’ toward the use of Code Switch by President SBY. Based on the results of analysis, it shows that there were three types of code switching found in President SBY’s interviews e.g. Intrasentential Switching, Intersentential Switching, and Tag Switching. In term of functions of code switching, nine functions were identified namely Reiteration, Personalization, Untranslatability, Substitution, Mitigating Message, Interjection, Emphasis, Clarification, and Quotation. Moreover, the findings from the questionnaires reveal that most respondents both from English and Indonesian Department perceived negatively to the use of Code Switching done by President SBY in the interview (17 persons). Some respondents who gave the negative attitude stated that the use of Code Switching did not provide the proper use of Indonesian according to EYD (ejaan yang disempurnakan), but it was considered to ruin Indonesian language structure. In contrast, the rest of respondents (13 persons) gave the positive attitude toward Code Switching since they claimed that Code Switching may increase the global vocabulary. Keywords: Code Switching, Interview with President SBY, Types of Code Switching, Function of Code Switching, Attitudes